1976
DOI: 10.1111/j.1365-2621.1976.tb14404.x
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF BEEF PATTIES CONTAINING soy PROTEIN, DURING 12‐MONTH FROZEN STORAGE

Abstract: Patties containing 20 or 30% of soy protein (textured or concentrate) were stored at -17°C and evaluated tri-monthly for 1 yr for effects of storage on organoleptic properties and chemical changes. Textured soy proteins from four manufacturers and concentrate from two manufacturers were tested. Fat content was about 20% for all patties. A 52-member panel of adults, from 18-60 yr of age, evaluated (without condiments) the 12 types of patties with soy and the all-meat patties. A 13-member panel evaluated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 9 publications
5
32
1
Order By: Relevance
“…TEIARS values moderately corre-- lated to overall color score (r = -0.36, PcO.05) and percent surface discoloration (r = 0.40, PcO.05). Our results appeared to agree with results of Kotula et al (1976) who showed soy extended ground beef had significantly lower TBA values than nonextended ground beef. Natural antioxidants of soybeans or antioxidants added during processing were cited as possible reasons for lower TBA values.…”
Section: Tbars Evaluationsupporting
confidence: 91%
“…TEIARS values moderately corre-- lated to overall color score (r = -0.36, PcO.05) and percent surface discoloration (r = 0.40, PcO.05). Our results appeared to agree with results of Kotula et al (1976) who showed soy extended ground beef had significantly lower TBA values than nonextended ground beef. Natural antioxidants of soybeans or antioxidants added during processing were cited as possible reasons for lower TBA values.…”
Section: Tbars Evaluationsupporting
confidence: 91%
“…The lower incidence of rancid flavor in these patties is attributable, in part, to the antioxidant properties inherent especially to soy flour (Hayes et al, 1977). However, in previous studies (Ziprin et al, 1981;Kotula et al, 1976) soy flour has not been found to differ in antioxidant properties from other forms of soy. Furthermore, characteristic soy-like flavors were most frequently reported in patties processed with soy flour, and they may have masked the presence of rancid flavors.…”
Section: Statistical Analysesmentioning
confidence: 81%
“…Many studies have compared sensory and cooking properties of all-beef patties and patties extended with one or two types of soy protein (Kotula et al, 1976;Smith et al, 1976;Bowers and Engler, 197.5). compared the sensory and cooking characteristics of all-beef patties and beef patties extended with 10% soy protein (flour, concentrate and isolate).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity contained in soy protein preparations has been well established (Bowers and Engler, 197.5;Kotula et al, 1976;Hayes et al, 1977;Thompson et al, 1978;Dignam et al, 1979;Ray et al, 1981). The source of the observed antioxidant activity in soy proteins has, however, only been partially defined.…”
Section: Introductionmentioning
confidence: 99%